Assessing the Correlation between Neighborhood Green Areas and the Perceived Mental Health of Residents in Metropolitan Areas - Kyung-A Choi; Mehdi Rezaei (Iranian Journal of Public Health, 2022)
Background: Urban parks play a noticeable role in city areas for making connections between nature and the residents of cities, especially from a mental health perspective. This paper investigated how the number and types of urban parks impact city residents' mental health.